2017
DOI: 10.1080/02640414.2017.1361895
|View full text |Cite
|
Sign up to set email alerts
|

Does elite success trigger mass participation in table tennis? An analysis of trickle-down effects in Germany, France and Austria

Abstract: There is a widespread belief that success at the elite level leads to increasing mass participation in sports. However, this assumption is merely supported by empirical evidence and is analyzed here for the case of table tennis. Therefore long-term data (1964-2014) on participation in Germany, France and Austria is statistically tested for effects of success by the countries' athletes at international competitions. Results indicate that no general trickle-down effect can be confirmed for table tennis in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…The potential for TDE is more likely to occur in conjunction with carefully planned and executed event leveraging strategies (e.g., [61][62][63]). Leveraging is underpinned by the idea that increased participation levels are more likely to result from the combined influence of staging an event and the implementation of interventions designed to promote sport opportunities [5].…”
Section: Event Leveraging Activitiesmentioning
confidence: 99%
“…The potential for TDE is more likely to occur in conjunction with carefully planned and executed event leveraging strategies (e.g., [61][62][63]). Leveraging is underpinned by the idea that increased participation levels are more likely to result from the combined influence of staging an event and the implementation of interventions designed to promote sport opportunities [5].…”
Section: Event Leveraging Activitiesmentioning
confidence: 99%
“…40,43,47 One study, which did not provide the age range of the studied population, observed a null effect of hosting elite sport events on sport memberships. 37 Negative, null, or mixed effects of hosting elite sport events on PA/sport practice at a large-scale level were observed in 1, 54 6, 30,33,41,50,60,63 and 2 studies, 48,59 respectively. Null or mixed effects of hosting elite sport events on PA/sport practice at local levels were observed in 5 30,36,50,62,63 and 8 studies, 31,[33][34][35]47,54,59,60 respectively; one study observed a positive effect of hosting elite sport events at local levels.…”
Section: Effect Of Hosting Elite Sport Events On Pa/sport Practice In...mentioning
confidence: 96%
“…51 The 6 studies that did not provide the age range of the studied population showed diverse results. Null or mixed effects of elite sport success on PA/sport practice were observed in 1 37 and 3 studies, 45,53,61 respectively; one study observed an increase in PA/ sport practice after elite sport success. 58 Two studies observed mixed lagged effects of elite sport success on PA/sport practice 57,61 ; one study observed a lagged increase in PA/sport practice after elite sport success.…”
Section: Effect Of Elite Sport Success On Pa/sport Practice In the Ge...mentioning
confidence: 99%
“…En los últimos años se han publicado algunos estudios en las áreas de política y gestión mediante el análisis de correlación o regresión para determinar la relación entre el éxito deportivo y las licencias deportivas principalmente en un único deporte (Frick y Wicker, 2016;Haut y Gaum, 2017). Los resultados de los estudios publicados son controvertidos; así varios investigadores identifican contra efectos en algunos deportes.…”
Section: La Función Inspiradora Del Deporte De éLiteunclassified